Kondisi Sosial Dan Ekonomi Petani Cabai Rawit Di Desa Tombasian Atas Satu Kecamatan Kawangkoan Barat Kabupaten Minahasa - Lumbantoruan, Marthin Romulus; Rumagit, Grace A.J.; Tarore, Melissa L.G. (AGRI-SOSIOEKONOMI, 2024)
The purpose of this study was to determine the social and economic conditions of cayenne pepper farmers in Tombasian Atas Satu Village, West Kawangkoan District, Minahasa Regency. This research was conducted for three months from July to September 2023, located in Tombasian Atas Satu Village, West Kawangkoan District, Minahasa Regency, North Sulawesi. The data collection method used in this research is primary data obtained directly through observations and interviews with cayenne pepper farmers in Tombasian Atas Village. Secondary data were obtained from literature related to the socio-economic conditions of cayenne pepper farmers or books, research journals, articles or data from local governments. The population in this study were all heads of families of cayenne pepper farmers in Tombasian Atas Satu Village, totaling 25 families. The data analysis method used in the research is descriptive analysis by processing data from the field into quantitative data in tabular form and then described so as to explain the social and economic conditions of farmers. The results showed that the social and economic conditions of cayenne pepper farmers in Tombasian Atas Satu Village were classified as good. The majority of farmers have higher education, farming knowledge gained from experience, and relatively few family dependents. The majority of farmers choose to seek treatment at the health center or doctor. The majority of farming experience is in the range of 0-5 years, the main source of capital comes from farmers themselves, the majority of farmers own their own land, and livelihood diversification helps reduce economic risk. Farmers' production and income ranged from 50-90 kg of cayenne pepper per month, with an income of IDR1.500.000 to IDR3.000.000.